IMPLEMENTASI KEBIJAKAN ASAS ULTIMUM REMEDIUM DALAM PENANGANAN TINDAK PIDANA DI BIDANG CUKAI PADA DIREKTORAT JENDERAL BEA DAN CUKAI - Yudhistira, Andreas Danar; Arimbhi, Pebriana (Jurnal Ilmu Administrasi Publik, 2025)
The implementation of the ultimum remedium principle on criminal acts in the field of excise at the DGCE emphasizes the reduction of potential state losses due to unscrupulous excise violators with the mechanism of imposing administrative sanctions in the form of fines. ultimum remedium is the concept of applying criminal law handling as the last resort in the problem handling process. This study aims to determine and analyze how the implementation of the ultimum remedium principle in handling excise crimes along with the obstacles and solutions to the implementation of the policy. The research methodology used is a qualitative method involving data collection techniques such as interviews, observations, and document studies to explore the experiences and perceptions of implementers and stakeholders. The results of this study showed that the policy implementation carried out by the Directorate General of Customs and Excise has not been maximized in the dimensions of communication, resources and bureaucratic structure, because there are still obstacles in its implementation. However, despite the obstacles found, this policy has an impact on the return of state revenue rights for violations in the excise sector through the mechanism of administrative sanctions (fines) excise.